Heterogeneous preferences and the individual change to alternative electricity contracts - Andreas Ziegler (Philipps-University Marburg, School of Business and Economics, 2018)
Based on data from a large-scale computer-based survey among more than 3700 German citizens, this paper empirically disentangles the determinants of the general change of electricity contracts and the specific change to green electricity contracts. Our econometric analysis reveals a strong relevance of behavioral factors and individual values and norms. For example, patience (which was measured by an incentivized experiment included in the survey) has a significantly positive effect on both general switches to alternative electricity contracts and specific switches to green electricity contracts. Furthermore, trust and (less robust) social preferences (also measured by an incentivized experiment) have additional significantly positive effects on the specific change to green electricity contracts. Our estimation results also imply an important role of political identification, i.e. an ecological policy orientation is strongly significantly positively correlated with the change to green electricity contracts. Furthermore, several household specific factors like relocation decisions as well as socio-demographic and socio-economic variables like household income are also relevant. The empirical analysis thus provides new explanation patterns for the phenomenon that relatively few households regularly change their electricity contracts and specifically switch to green electricity contracts, although they have high stated preferences for such changes. Our insights suggest several directions for policy and electricity suppliers to increase these switching rates. For example, the high importance of trust for the change to green electricity contracts suggests transparency initiatives of electricity suppliers to decrease concerns against renewable energies.
Keywords: A13; C93; D12; D91; Q41; Q42; Q50; 330; Switching electricity contracts; green electricity; behavioral factors; artefactual field experiments; individual values and norms